INFLUENCE OF RETAILING MIX TO CONSUMER’S DECISION TO SHOPPING AT PREMIUM DISTRO IN MALANG (STUDY AT PASTBRIK STORE AND TWENTY TWELVE PREMIUM STORE) - Prasetya, Aditya Wisnu; mijati, Noer (Jurnal Ilmiah Mahasiswa FEB, 2013)
INFLUENCE OF RETAILING MIX TO CONSUMER’S DECISION TO SHOPPING AT PREMIUM DISTRO IN MALANG (STUDY AT PASTBRIK STORE AND TWENTY TWELVE PREMIUM STORE). This study purposes to to know and analyze the significant influence between the variable of retail marketing mix to the consumer’s decision to shopping at Premium Distro in Malang. In this study, the factors that effect consumer’s decision are product, price, promotion, place, presentation, and personnel. The research was conducted at Pastbrik Store and Twenty Twelve Premium Store by using survey methodology. The respondents or sample was choosen as 105 samples based on purposive sampling, which the respondents taken by some criterias. The data were analyzed by  using SPSS 19(IBM SPSS 19). The result of this research showed that The result shows that dimension of retailing mix simultaneously influence the consumer’s decision to shopping at Premium Distro in Malang. Meanwhile, only variable product  that partially influence the consumer’s decision to shopping at Premium Distro in Malang. The most influential variable of retailing mix to the consumer’s decision to shopping at Premium Distro in Malang is Variable product. It indicate that retailing mix has significant influence to the consumer’s decision to shopping at Premium Distro in Malang, especially the variable product. Key words: Retailing Mix, product, price, promotion, place, presentation, and personnel, consumer’s decision, Premium Distro, Pastbrik Store, Twenty Twelve Premium Store